Design and Implementation of a Data Sharing Model for Improving Blockchain Technology - Xiaowei Wang (Advances in Multimedia)
With the continuous development of technology, the advancement of various data sharing technologies has gradually penetrated into various fields. Thus, data sharing and security are vital to realizing the value of the data. Nevertheless, the original data sharing model is not easily monitored for traces of electronic data use. In addition, the reluctance of data providers to share their data is also a problem. In order to address the issues of traditional centralized data sharing and management in terms of security and control, this research proposes the data sharing model based on blockchain technology, thereby enabling secure access to data. Furthermore, this study evaluates the model in terms of functionality and security. The results show that the blockchain-based data sharing model designed in this paper has great feasibility, security, controllability, and efficiency.